2018
DOI: 10.1002/ijc.31953
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fibroblasts (CAFs) promote the lymph node metastasis of esophageal squamous cell carcinoma

Abstract: Lymph node metastasis is a pathognomonic feature of spreading tumors, and overcoming metastasis is a challenge in attaining more favorable clinical outcomes. Esophageal cancer is an aggressive tumor for which lymph node metastasis is a strong poor prognostic factor, and the tumor microenvironment (TME), and cancer-associated fibroblasts (CAFs) in particular, has been implicated in esophageal cancer progression. CAFs play a central role in the TME and have been reported to provide suitable conditions for the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 58 publications
3
79
0
Order By: Relevance
“…As one of the important stromal cells in solid tumors, CAFs differentiate into fibroblasts that express α-SMA, playing a central role in promoting tumor growth and progression [17]. Many studies have shown that the accumulation of CAFs in tumor stroma accelerates metastasis [5,[18][19][20]. High expression of α-SMA was found both in GC tumors and CAFs, indicating a pathogenic role of fibroblasts in GC tumor.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the important stromal cells in solid tumors, CAFs differentiate into fibroblasts that express α-SMA, playing a central role in promoting tumor growth and progression [17]. Many studies have shown that the accumulation of CAFs in tumor stroma accelerates metastasis [5,[18][19][20]. High expression of α-SMA was found both in GC tumors and CAFs, indicating a pathogenic role of fibroblasts in GC tumor.…”
Section: Discussionmentioning
confidence: 99%
“…And the tumor invasion and metastasis are still the main causes for the patients' deaths. 1,3,5 In recent years, researches showed a sharp relationship between β-arrestin1 and pathological courses of various tumors. 19,20 This study revealed that the protein level of β-arrestin1 was drastically higher in ESCC tissues than in adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal squamous cell carcinoma (ESCC), the predominant type of esophageal carcinoma, carries a poor prognosis and a low survival rate. [1][2][3][4] Effective tumor markers will play an important role in early diagnosis, treatment monitoring and prognosis evaluation of ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…CAFs are fibroblasts in a state of continuous activation [120]. As one of the most important components of mesenchyme, CAFs play an important role in tumour growth, proliferation and metastasis [120,121]. In turn, tumour cells can promote fibroblast activation through feedback regulation [122].…”
Section: Circrnas and Cafsmentioning
confidence: 99%